The New Era of Cancer Immunotherapy: Targeting Myeloid-Derived Suppressor Cells to Overcome Immune Evasion - De Cicco, Paola; Ercolano, Giuseppe; Ianaro, Angela (Frontiers in Immunology, 2020)
Suppression of antitumor immune responses is one of the main mechanisms by which tumor cells escape from destruction by the immune system. Myeloid-derived suppressor cells (MDSCs) represent the main immunosuppressive cells present in the tumor microenvironment (TME) that sustain cancer progression. MDSCs are a heterogeneous group of immature myeloid cells with a potent activity against T-cell. Studies in mice have demonstrated that MDSCs accumulate in several types of cancer where they promote invasion, angiogenesis and metastasis formation and inhibit antitumor immunity. In addition, different clinical studies have shown that MDSCs levels in the peripheral blood of cancer patients correlates with tumor burden, stage and with poor prognosis in multiple malignancies. Thus, MDSCs are the major obstacle to many cancer immunotherapies and their targeting may be a beneficial strategy for improvement the efficiency of immunotherapeutic interventions. However, the great heterogeneity of these cells make their identification in human cancer very challenging. Since both the phenotype and mechanisms of action of MDSCs appear to be tumor-dependent, it is important to accurately characterized the precise MDSCs subsets that have clinical relevance in each tumor environment to more efficiently target them. In this review we summarize the phenotype and the the suppressive mechanisms of MDSCs populations expanded within different tumor contexts. Further, we discuss about their clinical relevance for cancer diagnosis and therapy.